Development of a human umbilical cord-derived mesenchymal stromal cell-based advanced therapy medicinal product to treat immune and/or inflammatory diseases - Miryam Mebarki (BMC, 2021)
Abstract Background Umbilical cord-derived mesenchymal stromal cells (UC-MSCs) revealed their key role in immune regulation, offering promising therapeutic perspectives for immune and inflammatory diseases. We aimed to develop a production process of an UC-MSC-based product and then to characterize UC-MSC properties and immunomodulatory activities in vitro, related to their clinical use and finally, to transfer this technology to a good manufacturing practice (GMP) compliant facility, to manufacture an advanced therapy medicinal product (ATMP). Methods Fifteen human umbilical cords (UCs) were collected to develop the production process. Three batches of UC-MSCs from a single donor were characterized at basal state and after in vitro pro-inflammatory stimulation by interferon-γ (IFNγ) and tumor necrosis factor-α (TNFα). Proliferation, immunophenotype, activation markers’ expression and the inhibition of T cell proliferation were assessed. Finally, this technology was transferred to a GMP-compliant facility to manufacture an UC-MSC-based ATMP, from a single donor, using the explant method followed by the establishment of master and work cell stocks. Results Twelve UCs were processed successfully allowing to isolate UC-MSCs with doubling time and population doubling remaining stable until passage 4. CD90, CD105, CD73, CD44, CD29, CD166 expression was positive; CD14, CD45, CD31, HLA-DR, CD40, CD80 and CD86 expression was negative, while CD146 and HLA-ABC expression was heterogeneous. Cell morphology, proliferation and immunophenotype were not modified by inflammatory treatment. Indoleamine 2,3-dioxygenase (IDO) expression was significantly induced by IFNγ and IFNγ + TNFα versus non-treated cells. Intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule 1 (VCAM-1) expression was induced significantly after priming. T cell proliferation was significantly decreased in the presence of UC-MSCs in a dose-dependent manner. This inhibitory effect was improved by IFNγ or IFNγ + TNFα, at UC-MSCs:PBMC ratio 1:10 and 1:30, whereas only IFNγ allowed to decrease significantly T cell proliferation at ratio 1:100. The manufacturing process of the UC-MSC-based ATMP was qualified and authorized by the French regulatory agency for clinical use (NCT04333368). Conclusion This work allowed to develop an investigational UC-MSC-based ATMP authorized for clinical use. Our results showed that an inflammatory environment preserves the biological properties of UC-MSCs with an improvement of their immunomodulatory functions.